Early re-emerging tremor after MRgFUS thalamotomy: case–control analysis of procedural and imaging features - Bruno, Federico; Badini, Pierfrancesco; Innocenzi, Antonio; Saporito, Gennaro; Catalucci, Alessia; Sucapane, Patrizia; Barile, Antonio; Cesare, Ernesto Di; Marini, Carmine; Pistoia, Francesca; Splendiani, Alessandra (Frontiers in Neurology, 2024)
Purpose: To identify possible prognostic factors determining early tremor relapse after MRgFUS thalamotomy in patients with essential tremor (ET) and Parkinson's disease (PD).Methods: 9 patients(6 ET, 3PD) who underwent Vim MRgFUS thalamotomy in a single institution and developed early re-emergent tremor were analyzed. A control group of patients matched pairwise for sex, pathology, age, disease duration and SDR was selected to compare the technical-procedural data and MR imaging evidence. MR imaging findings compared between groups included lesion shape and volume in multiparametric sequences, FA and ADC values derived from DTI and DWI sequences.Results: We did not find statistically significant differences in gender and age between the two groups. Technical and procedural parameters were also similar in both treatment groups. Concerning MRI analysis, we found lesions of similar size, but with greater caudal extension in the control group with stable outcomes, compared to patients with tremor relapse.In our analysis of early recurrences after thalamotomy with focused ultrasound, there were no technical and procedural differences, nor prognostic factors related to lesion size or ablation temperatures. Greater caudal extension of the lesion in patients without recurrence might suggest the importance of spatial consolidation during treatment.